Gut microbiota and uremic toxins produced in intestines in patients with chronic renal failure - Miloš Mitrović; Nada Dimković (Биомедицинска истраживања, 2018)
In recent years, academic publishing excited a considerable interest in gut microbiota and its role in human health maintenance. In patients with chronic renal failure, gut microbiota is altered due to increased blood urea nitrogen and metabolic acidosis, specific diet and therapy, as well as prolonged intestinal transit time. Protein-fermenting bacteria such as E. coli, Bacteroides and Ruminicoccus spp dominate gut microbiota in patients with chronic renal failure. Therefore, the key nephroand cardiovascular toxins, such as indoxyl-sulfate (IS) and p-cresyl-sulfate (PCS) are produced in the gut mucosa. The important impact of increased serum levels of IS and PCS on cardiovascular comorbidity and further deterioration of renal function has been witnessed by numerous observational and animal studies. There are several therapeutic strategies for lowering serum levels of IS and PCS as well as their toxic effect. The use of synbiotics, preand probiotics, in order to modulate gut microbiota is the most optimal solution currently used. Probiotic cultures of Bifidobacter and Lactobacillus have presented themselves as the ones with the greatest potential to limit the growth of protein-fermenting bacteria responsible for the production of uremic toxins. Nevertheless, there is still a need for more well-designed prospective interventional studies, as well as for controls with well-defined diet restrictions, in order to establish definitive value of this kind of therapy in patients with chronic renal failure.
Keywords: gut microbiota; chronic renal failure; uremic toxins